(untitled) (Ibrahim Cardiac Medical Journal, 2018)
Background & objective: Left bundle branch block (LBBB), resulting in an alteration of the normal sequence of activation in the left ventricle, commonly occurs in patients with underlying heart disease particularly coronary artery disease (CAD), but it may also be associated with progressive conducting system disease in an otherwise structurally normal heart. The aim of this study was to evaluate the clinical and angiographic profile of patients presenting with LBBB. Materials & Methods: This study was a cross-sectional observational study. A total of 542 patients of LBBB (as evident by ECG) who underwent coronary angiography from 1st September 2005 to 31st August 2016 were identified from the records of Cath Lab database of Ibrahim Cardiac Hospital & Research Institute and were selected for the study. LBBB was defined as a QRS complex duration ≥120 ms with a broad notched or slurred R wave in leads I, aVL, V5 and V6. Results: Majority (95.8%) of the patients was over 40 years of age with mean age being 59.7 ± 10.7 years (range: 25-95 years). Nearly 60% of the patients were male, 62.2% diabetic and 69.7% hypertensive. Over one-third (37.1%) of patients had moderate left ventricular (LV) systolic dysfunction (ejection fraction 30-44%) and 7% had severe LV systolic dysfunction. Over half (51.9%) had normal body mass index. Unstable angina (45.8%) was the most common indication for angiography. Other indications included non-ST segment elevation myocardial infarction (17.2%), ST segment elevation myocardial infarction (11.3%), stable coronary artery disease (SCAD) (9.8%), prior myocardial infarction (13.3%) and atypical chest pain (2.6%). Nearly 60% of the patients had obstructive coronary artery disease and the rest (40.6%) had normal epicardial coronaries on angiography. Among those with obstructive CAD, 4.1% had left main disease, 20.5% had triple vessel disease (TVD), 14.4% double vessel disease (DVD) and 9.5% single vessel disease (SVD). Conclusion: There is an optimum prevalence of CAD among LBBB patients, with TVD being predominant. LBBB cases with normal coronaries are no less. The latter cases suggest an alternative cause for LBBB. Thus, the usual diagnosis of CAD in patients with presumably new onset LBBB may be over-estimated in clinical practice. Ibrahim Card Med J 2016; 6 (1&2): 14-19